Governance and regulation of Artificial Intelligence from the first perspective of OpenAI - Fierro Rodríguez, Diego (2024)
The European Union Artificial Intelligence Act, set to come into force in August 2024, establishes a comprehensive regulatory framework for artificial intelligence in Europe, focusing on safety and trust. This legislation categorizes Artificial Intelligence systems by risk level, imposing specific requirements for each category, particularly for high-risk systems and unacceptable practices. The Act bans certain Artificial Intelligence practices and mandates rigorous obligations for high-risk Artificial Intelligence systems. Providers and deployers of Artificial Intelligence systems must adhere to these requirements, and the Act’s extraterritorial reach affects organizations outside the EU. Preparing for compliance involves classifying Artificial Intelligence systems and consulting with legal experts.